Literation Analysis of Young Mothers on Child Health - Lisa Lailatannur (Jurnal Multidisiplin Madani, 2023)
The purpose of this study was to analyze the literacy of young mothers on children's health. research This research uses mixed research (mixed method), researchers use tools that can be used as data and facts that are obtained comprehensively and thoroughly. The mixed method research model answers the problem formulation quantitatively and qualitatively. As for collecting data using several previous researchers who discussed similar themes, observation and documentation, with data analysis using a qualitative descriptive method which is a method that describes, interprets existing data and analyzes it. From the research above, it can be concluded that literacy for a mother really needs to be honed by following health programs that are usually carried out in each region, or you can use digital literacy, because of the importance of a mother to understand knowledge about child health